Profesionalisme Guru dan Peningkatan Mutu Pendidikan di Era Otonomi Daerah - Ahmadireja (Tarbiyah Departement collaboration with AMCA, 2014)
In order to achieve high quality in the field of education, the role of the teacher is very important and is very major. For that, the professionalism of the teacher should be enforced by way of the fulfillment of the terms of competencies that must be mastered by every teacher, both in the field of material science expertise and mastery of the methodology. Teachers should be responsible for their duties and must develop friendship with fellow teachers through participation and organization of teacher professional development. To achieve conditions that professional teachers, the teachers have to make quality orientation and professionalism of teachers as their work ethic and make it as a cornerstone of orientation behavior in the duties of his profession. Therefore, the code of ethics of the teaching profession must be upheld. During its development, it was realized that the teaching profession is not in an ideal position as expected, but should continue to strive towards the best. At the time of implementation of regional autonomy and decentralization of education along with the growth and development of information technology is very rapid, it is understood that many of the challenges and opportunities that must be overcome to be completed by the teacher education providers and institutions.